A high thermal conductivity current collector and a high safety lithium ion battery based on the current collector
High thermal current collectors are prepared through low-temperature carbonization and high-temperature graphitization, which solves the problem of thermal runaway in lithium-ion batteries and achieves high safety and excellent heat dissipation performance of the battery.
Patent Information
- Application Number
- CN202211557673.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-12-06
AI Technical Summary
Existing lithium-ion batteries are prone to thermal runaway events under high charge states, leading to fires, explosions and toxic gases, hindering the commercialization process of lithium-ion batteries.
Thermodynamic unstable carbon atoms were converted into graphite crystal structures by using two heating treatments of low-temperature carbonization and high-temperature graphitization, and a current collector with high thermal conductivity, flame retardant effect and high mechanical strength were prepared, and applied to lithium-ion batteries.
It effectively reduces the internal temperature of the battery, weakens chemical side reactions, avoids fire and explosion caused by thermal runaway, and improves the heat dissipation performance and safety of the battery.
Smart Images

Figure CN115732702B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a high-thermal-conductivity current collector and a high-safety lithium ion battery based on the current collector. Background Art
[0002] New energy storage batteries, especially lithium-ion batteries, play an increasingly important role in the development of human civilization, such as portable and wearable electronic products, power grid systems and electric vehicles. In recent years, in order to further improve the range of driving, the ternary nickel-rich cathode material Li[Ni 0.5 Mn 0.2 Co 0.3 ]O2(NCM523), Li[Ni 0.6 Mn 0.2 Co 0.2 ]O2(NCM622), Li[Ni 0.8 Mn 0.1 Co 0.1 ]O2 (NCM811) and other materials are widely used due to their high energy density. However, the resulting thermal runaway events of lithium-ion batteries also occur frequently, especially under high charge conditions, causing more and more catastrophic casualties and property losses, seriously hindering the commercialization of lithium-ion batteries.
[0003] Many typical works have been reported on improving the safety of lithium-ion batteries, including adding flame retardant components to current collectors, diaphragms or electrolytes, preparing diaphragms or gel polymer electrolytes whose structures are not easy to shrink at high temperatures, using phase change materials as temperature regulating diaphragms, etc. Although these methods can reduce the risk of thermal runaway to a certain extent, there are still some difficulties in their actual implementation. First, the synthesis process is too complicated to be mass-produced. Second, most batteries used for safety research have a capacity of less than 1.5Ah, which is unreliable for reference in actual research. Third, there is little research on the temperature distribution inside the battery during rapid charging and discharging. Finally, there is a lack of systematic research on battery safety from the fundamental aspect of heat dissipation in lithium-ion batteries.
[0004] In the complex multi-component system of lithium-ion batteries, the current collector is in close contact with the active material and plays a vital role in the heat dissipation of the entire battery. Commercial current collectors such as copper foil and aluminum foil have poor thermal conductivity (aluminum foil: 166.2W m -1 K -1 , copper foil: 185.7W m -1 K -1), which is less effective in battery heat transfer. Especially under a series of harsh conditions such as thermal abuse and rapid charge and discharge, batteries assembled with aluminum foil and copper foil can easily concentrate heat inside the battery, thereby inducing a series of exothermic reactions, such as decomposition of the solid electrolyte interphase, membrane shrinkage, and chemical crosstalk between the negative electrode, electrolyte, and positive electrode. In particular, aluminum foil can even burn and release heat at high temperatures, thereby exacerbating the degree of thermal runaway. If the generated heat cannot be dissipated in time, the temperature and gas pressure in the battery will rise rapidly, eventually leading to fire, explosion, and the generation of toxic gases. Therefore, it is urgent to find a current collector with high thermal conductivity, high stability and flame retardant effect. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art, to produce a current collector with high thermal conductivity, high stability and flame retardant effect, and to use the current collector to produce a high-safety lithium-ion battery.
[0006] The present invention is achieved in that:
[0007] The present invention provides a high thermal conductivity current collector, which is prepared by the following steps:
[0008] The precursor material is made into a precursor film, the precursor film is subjected to low-temperature carbonization and high-temperature graphitization heat treatment to obtain a graphitized foam material, and further calendering is performed to obtain a current collector with high thermal conductivity;
[0009] The conductivity of the prepared high thermal conductivity current collector is 1.0×10 5 -2.5×10 6 S m -1 , thermal conductivity is 1200-1600W m -1 K -1 , thickness is 5-500 μm, volume density is 1-10 mg cm -3 , mechanical strength is 10-200MPa.
[0010] The precursor material is made into a precursor film, the precursor film is carbonized and cracked at low temperature, and then graphitized at high temperature to use thermal activation to achieve an orderly transformation of the thermodynamically unstable carbon atoms from a chaotic layer structure to a graphite crystal structure. The graphitized foam is then calendered into a high-density and high-crystalline graphite film to obtain a high thermal conductivity current collector that can prevent oxygen from entering the graphite structure and has high thermal conductivity and flame retardant properties. Finally, the high thermal conductivity current collector is applied to lithium-ion batteries.
[0011] Furthermore, the precursor material may be carbon-containing organic materials such as polyimide, graphene oxide, aramid fiber, poly(p-phenylene benzobisoxazole), etc.
[0012] Furthermore, the concentration of the precursor is 0.01-50 mg / mL, and the method used to make the precursor into a membrane is one of vacuum filtration, doctor blade coating, suspension evaporation, spray coating or spin coating.
[0013] Furthermore, during the heat treatment, the carbonization temperature is 500-2000°C, the graphitization temperature is 2000-3500°C, the heating rate is 0.2-20°C / min, the carbonization time is 5-15h, and the graphitization time is 1-20h. In this scheme, two heating heat treatments are used, carbonization at 500-2000°C and graphitization at 2000-3500°C.
[0014] Furthermore, the heat treatment process is carried out in an inert gas atmosphere, and the flow rate of the inert gas is 5 to 500 ml / min.
[0015] Furthermore, the calendering pressure is 5-200 MPa, and the calendering time is 1-10 h.
[0016] The present invention also provides a high-safety lithium-ion battery based on the above-mentioned high thermal conductivity current collector, comprising a positive electrode plate, a negative electrode plate, a separator, an electrolyte and an outer packaging material, at least one of the positive electrode plate and the negative electrode plate is made of the above-mentioned high thermal conductivity current collector, and the maximum capacity of the battery is not less than 1.5Ah.
[0017] Specifically, when assembling the battery, the battery can be divided into the following three situations: (1) the positive electrode collector is a high thermal conductivity collector and the negative electrode collector is a copper foil; (2) the positive electrode collector is an aluminum foil and the negative electrode collector is a high thermal conductivity collector; (3) the positive electrode collector is a high thermal conductivity collector and the negative electrode collector is a high thermal conductivity collector. When the battery encounters extreme environmental tests such as needle puncture during use, based on the high thermal conductivity and flame retardant properties of the current collector, the internal temperature of the battery can be effectively reduced, chemical side reactions can be weakened, and thus fire and explosion caused by thermal runaway of the battery can be avoided. In addition, when the battery is in the process of rapid charge and discharge, the ultra-high thermal conductivity of the current collector can quickly transfer the heat inside the battery, thereby making the heat distribution inside the battery more uniform and eliminating the safety hazards caused by local heat concentration. Therefore, the battery is a high-safety lithium-ion battery.
[0018] Furthermore, the surface of the high thermal conductivity current collector is coated with positive electrode slurry or negative electrode slurry, and is baked, rolled, and cut into pieces to form positive electrode sheets or negative electrode sheets.
[0019] Furthermore, the battery positive electrode material is lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate, and the ternary material includes LiNi 1 / 3Co 1 / 3 Mn 1 / 3 O2(NCM111), LiNi 0.5 Co0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.7 Co 0.15 Mn 0.15 、LiNi 0.8 Co 0.1 Mn 0.1 (NCM811), LiNi 0.85 Co 0.075 Mn 0.075 The negative electrode material of the battery is one of graphite-based materials, silicon-based materials, tin-based materials or titanium-based materials.
[0020] Furthermore, the welding method of the high thermal conductivity current collector and the metal pole ear on the battery is brazing, including resistance welding, laser welding, electron beam welding and other welding methods, and the battery type is one of a button battery, a cylindrical battery, a square shell battery and a soft pack battery. During assembly, the electrode made by coating the high thermal conductivity current collector with slurry is welded and fixed to the metal pole ear on the battery, and the battery can be made into a variety of forms, all of which have high safety.
[0021] The present invention has the following beneficial effects:
[0022] 1. The present invention realizes the orderly transformation of thermodynamically unstable carbon atoms from a chaotic layer structure to a graphite crystal structure by double heating of low-temperature carbonization and high-temperature graphitization. The obtained current collector has a dense and continuous carbon layer structure, and its chemical thermal stability in the air is better than that of traditional aluminum foil and copper foil. It can prevent oxygen from entering the interior of the graphite material, making it difficult for the fire to spread. Under extreme puncture conditions, it will not catch fire or explode, and thermal runaway can be effectively avoided. Based on the chemical inertness of the current collector, the present invention enables the battery based on the high thermal conductivity current collector to have high safety performance.
[0023] 2. The lithium-ion battery of the present invention adopts a material with ultra-high thermal conductivity (1200-1600W m -1 K -1 ) film as a current collector, compared with lithium ion batteries using copper foil and aluminum foil with lower thermal conductivity, the lithium ion battery in the present invention has better heat dissipation performance. During the rapid charge and discharge process, the local heat can be quickly transferred to the remaining materials and dispersed, eliminating the safety hazard caused by the internal heat concentration of the battery. The present invention is based on the ultra-high thermal conductivity of the graphite film, so that the battery based on the high thermal conductivity current collector has high safety performance during normal charge and discharge.
[0024] 3. The high thermal conductivity current collector provided by the present invention has good flexibility and is lighter than commercial copper foil and aluminum foil. As a current collector for lithium-ion batteries, it can significantly reduce the weight of the battery and improve the energy density of the lithium-ion battery.
[0025] 4. The lithium-ion battery system of the present invention does not change the electrochemical system of the existing battery, does not sacrifice the electrochemical performance of the battery, and the preparation process is the same as the current lithium-ion battery production process, and the process can be used without building a new production line. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 This is a surface scanning electron microscope image of a high thermal conductivity current collector prepared in an embodiment of the present invention;
[0028] Figure 2 This is a cross-sectional scanning electron microscope image of a high thermal conductivity current collector prepared in an embodiment of the present invention;
[0029] Figure 3 is the XRD spectrum of the high thermal conductivity current collector prepared in the embodiment of the present invention;
[0030] Figure 4 This is the Raman spectrum of the high thermal conductivity current collector prepared in the embodiment of the present invention;
[0031] Figure 5 This is an infrared thermal imager thermal conductivity diagram of the high thermal conductivity current collector prepared in an embodiment of the present invention;
[0032] Figure 6 This is a comparison chart of the thermal stability of the high thermal conductivity current collector prepared in the embodiment of the present invention and copper foil and aluminum foil;
[0033] Figure 7 This is a comparison chart of the rate performance of a lithium-ion soft-pack battery based on a high thermal conductivity current collector and a lithium-ion soft-pack battery based on aluminum foil and copper foil prepared in an embodiment of the present invention;
[0034] Figure 8 This is a cycle performance diagram of a lithium-ion battery based on a high thermal conductivity current collector prepared in an embodiment of the present invention;
[0035] Fig. 9 This is a comparison chart of the puncture safety of the soft-pack batteries prepared in the embodiments of the present invention. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0038] Example 1
[0039] 1. Preparation of a high thermal conductivity current collector: using graphene oxide as a precursor material, uniformly dispersing it in an aqueous solution at a concentration of 30 mg / mL; preparing the graphene oxide into a film by a doctor blade coating method, and drying it at 60° C. for 10 h to obtain a graphene oxide film;
[0040] The obtained graphene oxide film is placed in a carbonization furnace and heated to 1200°C at a heating rate of 10°C / min in an argon atmosphere, kept warm for 5 hours, and then naturally cooled to complete the carbonization process. The carbonized reduced graphene oxide film is then placed in a graphitization furnace and heated to 2850°C at a heating rate of 10°C / min in an argon atmosphere, kept warm for 2 hours, and then naturally cooled in an argon gas flow to complete graphitization and obtain graphitized foam;
[0041] The graphitized foam was rolled on a calender at 100 MPa for 2 h, and then rolled to obtain a dense and smooth high thermal conductivity thin film current collector. The conductivity of the obtained high thermal conductivity current collector is 2.5×10 5 S m -1 , thermal conductivity is 1200W m -1 K -1 , thickness is 20 μm, volume density is 2 mg cm -3 , the mechanical strength is 40MPa.
[0042] 2. Preparation of lithium-ion batteries: The surface of the prepared high thermal conductivity current collector is coated with lithium iron phosphate positive electrode slurry, and the positive electrode sheet is made after baking, rolling and cutting; copper foil is used as the negative electrode current collector, and the surface is coated with graphite negative electrode slurry, and the negative electrode sheet is made after baking, rolling and cutting; the positive electrode sheet, the negative electrode sheet and the separator are wound to form a battery cell; then the multi-layer high thermal conductivity positive electrode current collector and the aluminum electrode ear are resistance welded, and the negative electrode current collector copper foil and the copper electrode ear are conventionally ultrasonically spot welded, and finally the electrolyte is injected and assembled with the outer packaging material as required to form a lithium-ion battery with positive electrode current collector replacement.
[0043] Example 2
[0044] 1. Preparation of a high thermal conductivity current collector: using graphene oxide as a precursor material, uniformly dispersing it in an aqueous solution at a concentration of 2 mg / mL; preparing the graphene oxide dispersion into a film by a suspension evaporation method, and drying it at 60° C. for 10 h to obtain a graphene oxide film;
[0045] The obtained graphene oxide film is placed in a carbonization furnace and heated to 1200°C at a heating rate of 10°C / min in an argon atmosphere, kept warm for 5 hours, and then naturally cooled to complete the carbonization process. The carbonized reduced graphene oxide film is then placed in a graphitization furnace and heated to 2850°C at a heating rate of 10°C / min in an argon atmosphere, kept warm for 2 hours, and then naturally cooled in an argon gas flow to complete graphitization and obtain graphitized foam;
[0046] The obtained foam was placed on a calender and calendered at 100 MPa for 2 hours. After winding, a dense and smooth high thermal conductivity current collector was obtained. The conductivity of the obtained high thermal conductivity current collector was 2.5×10 5 S m -1 , thermal conductivity is 1400W m -1 K -1 , thickness is 40μm, volume density is 4mg / cm 3 , the mechanical strength is 60MPa.
[0047] 2. Preparation of lithium-ion batteries: The surface of the prepared high thermal conductivity current collector is coated with lithium iron phosphate positive electrode slurry, and the positive electrode sheet is made after baking, rolling and cutting; copper foil is used as the negative electrode current collector, and the surface is coated with graphite negative electrode slurry, and the negative electrode sheet is made after baking, rolling and cutting; the positive electrode sheet, the negative electrode sheet and the separator are wound to form a battery cell; then the multi-layer high thermal conductivity positive electrode current collector and the aluminum electrode ear are resistance welded, and the negative electrode current collector copper foil and the copper electrode ear are conventionally ultrasonically spot welded, and finally the electrolyte is injected and assembled with the outer packaging material as required to form a lithium-ion battery with positive electrode current collector replacement.
[0048] Example 3
[0049] 1. Preparation of high thermal conductivity current collector: using dibasic anhydride and diamine as precursor materials, uniformly dispersing them in a polar organic solvent solution with a concentration of 20 mg / mL, scraping the polyimide precursor dispersion on the substrate by scraper coating, and drying at 300°C for 8 hours to obtain a polyimide film;
[0050] The obtained polyimide film is placed in a carbonization furnace and heated to 1300°C at a heating rate of 10°C / min in an argon atmosphere, kept warm for 5 hours, and then naturally cooled to complete the carbonization process. The carbonized polyimide film is then placed in a graphite furnace and heated to 3000°C at a heating rate of 10°C / min in an argon atmosphere, kept warm for 2 hours, and then naturally cooled in an argon gas flow to complete graphitization and obtain graphitized foam;
[0051] The obtained foam was placed on a static press and rolled for 2 hours at 200 MPa. After winding, a dense and smooth high thermal conductivity current collector was obtained. The conductivity of the obtained high thermal conductivity current collector was 1.3×10 6 S m -1 , thermal conductivity is 1200W m -1 K -1 , thickness is 20 μm, volume density is 2 mg cm -3 , the mechanical strength is 60MPa.
[0052] 2. Preparation of lithium-ion batteries: using the above-prepared high thermal conductivity current collector as the positive electrode current collector, coating the surface with lithium cobalt oxide positive electrode slurry, baking, rolling, and cutting to form a positive electrode sheet; using the above-prepared high thermal conductivity current collector as the negative electrode current collector, coating the surface with silicon-carbon negative electrode slurry, baking, rolling, and cutting to form a negative electrode sheet; winding the positive electrode sheet, the negative electrode sheet, and the separator to form a battery core; then electron beam welding the multi-layer high thermal conductivity positive electrode current collector to the aluminum pole ear, and electron beam welding the multi-layer high thermal conductivity negative electrode current collector to the copper pole ear, and finally injecting the electrolyte, and assembling with the outer packaging material as required to form a lithium-ion battery in which the positive electrode collector and the negative electrode collector can be replaced at the same time.
[0053] Example 4
[0054] 1. Preparation of high thermal conductivity current collector: Aramid fiber is used as a precursor material, which is dispersed and cracked in an organic solvent at a concentration of 0.8 mg / mL. The aramid nanofiber dispersion is filtered into a membrane by vacuum filtration and dried at 60°C for 10 hours to obtain an aramid cellulose membrane.
[0055] The obtained aramid cellulose membrane is placed in a carbonization furnace and heated to 1200°C at a heating rate of 10°C / min under an argon atmosphere, kept warm for 5 hours, and then naturally cooled to complete the carbonization process. The carbonized aramid cellulose membrane is then placed in a graphite furnace and heated to 3200°C at a heating rate of 10°C / min under an argon atmosphere, kept warm for 6 hours, and then naturally cooled in an argon gas flow to complete graphitization and obtain graphitized foam.
[0056] Finally, the obtained foam was placed on a static press and rolled at 150 MPa for 4 hours, and then rolled to obtain a dense and smooth high thermal conductivity current collector. The conductivity of the obtained high thermal conductivity current collector is 2.5×106 S m -1 , thermal conductivity is 1200W m -1 K -1 , thickness is 27 μm, volume density is 3 mg cm -3 , the mechanical strength is 60MPa.
[0057] 2. Preparation of lithium-ion batteries: Use aluminum foil as the positive electrode current collector, apply NCM811 positive electrode slurry on the surface, bake, roll and cut to make positive electrode sheets; use the high thermal conductivity current collector prepared above as the negative electrode current collector, apply graphite negative electrode slurry on the surface, bake, roll and cut to make negative electrode sheets; wind the positive electrode sheets, negative electrode sheets and separators to form a battery cell; then perform conventional ultrasonic spot welding on the positive electrode current collector aluminum foil and the aluminum pole ear, perform resistance welding on the multi-layer high thermal conductivity negative electrode current collector and the copper pole ear, and finally inject electrolyte and assemble with the outer packaging material as required to form a lithium-ion battery with negative electrode current collector replacement
[0058] Example 5
[0059] 1. Preparation of high thermal conductivity current collector: using poly (p-phenylene benzobisoxazole) as a precursor material, uniformly dispersing it in an organic solution at a concentration of 0.5 mg / mL, spraying the poly (p-phenylene benzobisoxazole) precursor on a substrate by a spraying method, and drying at 80° C. for 12 hours to obtain a poly (p-phenylene benzobisoxazole) fiber film;
[0060] The obtained poly(p-phenylene benzobisoxazole) fiber membrane is placed in a carbonization furnace and heated to 1400°C at a heating rate of 10°C / min in an argon atmosphere, kept warm for 5 hours, and then naturally cooled to complete the carbonization process. The carbonized poly(p-phenylene benzobisoxazole) fiber membrane is then placed in a graphite furnace and heated to 3200°C at a heating rate of 10°C / min in an argon atmosphere, kept warm for 8 hours, and then naturally cooled in an argon gas flow to complete graphitization and obtain graphitized foam.
[0061] Finally, the obtained foam was placed on a static press and rolled at 200 MPa for 10 hours, and then rolled to obtain a dense and smooth high thermal conductivity current collector. The conductivity of the obtained high thermal conductivity current collector is 5×10 5 S m -1 , thermal conductivity is 1200W m -1 K -1 , thickness is 20 μm, volume density is 2 mg cm -3 , the mechanical strength is 60MPa.
[0062] 2. Preparation of lithium-ion battery: Use the above-prepared high thermal conductivity current collector as the positive current collector, apply NCM811 positive electrode slurry on the surface, bake, roll and cut to make positive electrode sheet; use the above-prepared high thermal conductivity current collector as the negative current collector, apply graphite negative electrode slurry on the surface, bake, roll and cut to make negative electrode sheet, wind the positive electrode sheet, negative electrode sheet and separator to form a battery core; then, resistance weld the multi-layer high thermal conductivity positive current collector with aluminum pole ear, and resistance weld the multi-layer high thermal conductivity negative current collector with copper pole ear. Finally, inject electrolyte, assemble with outer packaging materials as required to form a lithium-ion battery in which the positive current collector and negative current collector can be replaced at the same time.
[0063] Example 6
[0064] 1. Preparation of a high thermal conductivity current collector: using graphene oxide as a precursor material, uniformly dispersing it in an aqueous solution at a concentration of 0.5 mg / mL; spin coating the graphene oxide solution to form a film by spin coating, and drying at 60° C. for 10 h to obtain a graphene oxide film;
[0065] The obtained graphene oxide film is placed in a carbonization furnace and heated to 1400°C at a heating rate of 10°C / min in an argon atmosphere, and then naturally cooled to complete the carbonization process. The carbonized reduced graphene oxide film is then placed in a graphite furnace and heated to 3200°C at a heating rate of 10°C / min in an argon atmosphere, and then naturally cooled in an argon gas flow to complete graphitization and obtain graphitized foam;
[0066] Finally, the obtained foam was placed on a static press and rolled at 200 MPa for 10 hours, and then rolled to obtain a dense and smooth high thermal conductivity current collector. The conductivity of the obtained high thermal conductivity current collector is 1.3×10 6 S m -1 , thermal conductivity is 1600W m -1 K -1 , thickness is 20 μm, volume density is 2 mg cm -3 , the mechanical strength is 60MPa.
[0067] 2. Preparation of lithium-ion battery: Use the above-prepared high thermal conductivity current collector as the positive current collector, apply NCM811 positive electrode slurry on the surface, bake, roll and cut to make positive electrode sheet; use the above-prepared high thermal conductivity current collector as the negative current collector, apply graphite negative electrode slurry on the surface, bake, roll and cut to make negative electrode sheet, wind the positive electrode sheet, negative electrode sheet and separator to form a battery core; then, resistance weld the multi-layer high thermal conductivity positive current collector with aluminum pole ear, and resistance weld the multi-layer high thermal conductivity negative current collector with copper pole ear. Finally, inject electrolyte, assemble with outer packaging materials as required to form a lithium-ion battery in which the positive current collector and negative current collector can be replaced at the same time.
[0068] Test example
[0069] The high thermal conductivity current collectors prepared in Examples 1 to 6 were subjected to various tests such as XRD, Raman spectroscopy, SEM, and infrared thermal imaging (the results obtained in Examples 1 to 6 were very different, and the high thermal conductivity current collector prepared in Example 1 was selected for characterization), and the results are as follows:
[0070] like Figure 1 As shown in , the surface of the high thermal conductivity current collector is covered with micro-wrinkles, which is conducive to the adhesion of the electrode material on the current collector surface; Figure 2 As shown, the high thermal conductivity current collector has a high degree of densification in the cross-sectional direction and is arranged in layers in parallel. The dense and continuous carbon layer structure on the surface and between the layers of the high thermal conductivity current collector can prevent oxygen from entering the interior of the graphite material, thereby effectively avoiding thermal runaway under extreme needle puncture conditions.
[0071] like Figure 3 As shown in Figure 1, the X-ray diffraction peak of the high thermal conductivity current collector is sharp and strong, and the interlayer spacing of graphite corresponding to the (002) diffraction peak is 0.334 nm; Figure 4 As shown, the Raman spectrum of the obtained high thermal conductivity current collector shows that I D / I G =0.03, indicating that the current collector has an extremely high degree of graphitization and the defects are repaired.
[0072] like Figure 5 As shown in the figure, the thermal conductivity image of the high thermal conductivity collector under the infrared thermal imager, the bottom of the three film materials are heated on a heating table at 65°C. Compared with copper foil and aluminum foil, the overall temperature distribution of the high thermal conductivity collector is more uniform, and its heat transfer rate is significantly higher than that of copper foil and aluminum foil; Figure 6 As shown, during the heating process of the alcohol lamp's outer flame, the aluminum foil is immediately corroded by the heat flow into a porous and fragile structure, and the copper foil is directly oxidized and releases heat under the flame heating. The high thermal conductivity current collector will not burn even after being heated for 10 minutes, and can maintain its original flexibility.
[0073] The performance of the lithium ion batteries prepared in Examples 1 to 6 was tested, and the results were as follows:
[0074] like Figure 7As shown, a is the charge and discharge rate performance diagram of lithium-ion soft-pack batteries based on aluminum foil and copper foil, and b is the charge and discharge rate performance diagram of lithium-ion soft-pack batteries based on high thermal conductivity current collectors. The battery based on high thermal conductivity current collectors has a capacity of 149.1 mAh / g at a current density of 0.1C and a capacity of 88.9 mAh / g at a current density of 5C. However, the battery based on copper foil and aluminum foil current collectors is slightly lower, with a discharge capacity of 143.4 mAh / g at a current density of 0.1C and a discharge capacity of only 86.3 mAh / g at a current density of 5C. More importantly, the battery based on high thermal conductivity current collectors has a smaller polarization voltage at a high rate of 5C. The above excellent rate performance of batteries based on high thermal conductivity current collectors can be attributed to the rich micro-wrinkle structure on the surface of the prepared current collector, which can ensure a larger specific surface area, enhance the contact and adhesion ability between the electrode material and the current collector, and reduce the charge transfer resistance;
[0075] like Figure 8 As shown in the figure, the battery based on the high thermal conductivity current collector can maintain stable cycle performance even after 500 cycles at 1C, and the capacity basically does not decay. After 500 cycles, its stable capacity remains at 131.4mAh / g, and the coulombic efficiency is close to 100%, showing excellent cycle performance.
[0076] The above electrochemical properties indicate that the high-safety lithium-ion battery based on a high thermal conductivity current collector involved in the present invention does not sacrifice its electrochemical performance, and has great advantages and prospects compared to other battery systems that sacrifice electrochemical performance to improve safety.
[0077] The soft-pack battery prepared in Example 3 of the present invention and the soft-pack battery based on the copper foil and aluminum foil current collector were selected for acupuncture experiments. The design capacity of the two soft-pack batteries was 2Ah. Before acupuncture, the two soft-pack batteries were fully charged. The results are as follows: Fig. 9 As shown, the soft-pack batteries based on copper foil and aluminum foil current collectors caught fire and exploded during the puncture process, while the assembled soft-pack batteries based on high thermal conductivity current collectors only produced a small amount of smoke during the puncture process, without open flames or explosions, and the safety performance was greatly improved.
[0078] In summary, in the manufacturing process of the current collector, the present invention uses positive and negative current collectors with high electrical conductivity and high thermal conductivity, and the positive and negative active materials are coated on the surface of the current collector, and assembled with the diaphragm and outer packaging materials to form a rechargeable lithium-ion battery. When the battery encounters extreme environmental tests such as needle puncture during use, based on the high thermal conductivity and flame retardant properties of the current collector, the internal temperature of the battery can be effectively reduced, and chemical side reactions can be weakened, thereby avoiding fire and explosion caused by thermal runaway of the battery. In addition, when the battery is in the process of rapid charge and discharge, the ultra-high thermal conductivity of the current collector can quickly transfer the heat inside the battery, thereby making the heat distribution inside the battery more uniform, eliminating the safety hazards caused by local heat concentration.
[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high thermal conductivity current collector, characterized in that: Prepared by the following steps: The precursor material is made into a precursor film, the precursor film is subjected to low-temperature carbonization and high-temperature graphitization heat treatment to obtain graphitized foam, and the high thermal conductivity current collector is obtained by calendering; the precursor material is graphene oxide; The heat treatment process is carried out under an inert gas atmosphere. During the heat treatment process, the carbonization temperature is 1400°C, the graphitization temperature is 3200°C, the carbonization time is 5h, and the graphitization time is 8h; the calendering pressure is 200MPa, and the calendering time is 10h; The conductivity of the prepared high thermal conductivity current collector is 1.3×10 6 Sm -1 , thermal conductivity is 1600W m -1 K -1 , thickness is 20 μm, volume density is 2 mg cm -3 , the mechanical strength is 60MPa.
2. The high thermal conductivity current collector according to claim 1, characterized in that: The concentration of the precursor is 0.01-50 mg / mL, and the method used to make the precursor into a membrane is one of vacuum filtration, scraper coating, suspension evaporation, spraying or spin coating.
3. The high thermal conductivity current collector according to claim 1, characterized in that: During the heat treatment process, the heating rate is 0.2-20°C / min.
4. The high thermal conductivity current collector according to claim 3, characterized in that: The flow rate of the inert gas during the heat treatment process is 5 to 500 ml / min.
5. A high-safety lithium-ion battery based on the high thermal conductivity current collector according to any one of claims 1 to 4, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and an outer packaging material, at least one of the positive electrode sheet and the negative electrode sheet is made of a high thermal conductivity collector as claimed in any one of claims 1 to 4, and the maximum capacity of the battery is not less than 1.5Ah.
6. The high-safety lithium-ion battery according to claim 5, characterized in that: The positive electrode slurry or negative electrode slurry is coated on the surface of the high thermal conductivity current collector, and is baked, rolled, and cut into pieces to form a positive electrode sheet or a negative electrode sheet.
7. The high-safety lithium-ion battery according to claim 6, characterized in that: The positive electrode material of the battery is lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate, and the ternary material includes LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM111), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.7 Co 0.15 Mn 0.15 、LiNi 0.8 Co 0.1 Mn 0.1 (NCM811), LiNi 0.85 Co 0.075 Mn 0.075 The negative electrode material of the battery is one of graphite-based materials, silicon-based materials, tin-based materials or titanium-based materials.
8. The high-safety lithium-ion battery according to claim 7, characterized in that: The welding method of the high thermal conductivity current collector and the metal ear on the battery is brazing, including resistance welding, laser welding or electron beam welding, and the battery type is one of a button battery, a cylindrical battery, a square shell battery and a soft pack battery.
9. A high thermal conductivity current collector, characterized in that: Prepared by the following steps: The precursor material is made into a precursor film, the precursor film is subjected to low-temperature carbonization and high-temperature graphitization heat treatment to obtain graphitized foam, and the high thermal conductivity current collector is obtained by calendering; The precursor material is aramid fiber or poly(p-phenylene benzobisoxazole). During the heat treatment, the carbonization temperature is 500-2000° C., the graphitization temperature is 2000-3500° C., the heating rate is 0.2-20° C. / min, the carbonization time is 5-15 hours, and the graphitization time is 1-20 hours. The conductivity of the prepared high thermal conductivity current collector is 1.0×10 5 -2.5×10 6 Sm -1 , thermal conductivity is 1200-1600Wm -1 K -1 , thickness is 5-500μm, volume density is 1-10mg / cm 3 , mechanical strength is 10-200MPa.
10. The high thermal conductivity current collector according to claim 9, characterized in that: The concentration of the precursor is 0.01-50 mg / mL, and the method used to make the precursor into a membrane is one of vacuum filtration, scraper coating, suspension evaporation, spraying or spin coating.
11. The high thermal conductivity current collector according to claim 9, characterized in that: The heat treatment process is carried out in an inert gas atmosphere, and the flow rate of the inert gas is 5 to 500 ml / min.
12. The high thermal conductivity current collector according to claim 9, characterized in that: The calendering pressure is 5-200MPa, and the calendering time is 1-10h.
13. A high-safety lithium-ion battery based on the high thermal conductivity current collector according to any one of claims 9 to 12, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and an outer packaging material, wherein at least one of the positive electrode sheet and the negative electrode sheet is made of a high thermal conductivity collector as claimed in any one of claims 9 to 12, and the maximum capacity of the battery is not less than 1.5Ah.
14. The high-safety lithium-ion battery according to claim 13, characterized in that: The positive electrode slurry or negative electrode slurry is coated on the surface of the high thermal conductivity current collector, and is baked, rolled, and cut into pieces to form a positive electrode sheet or a negative electrode sheet.
15. The high-safety lithium-ion battery according to claim 14, characterized in that: The positive electrode material of the battery is lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate, and the ternary material includes LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM111), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.7 Co 0.15 Mn 0.15 、LiNi 0.8 Co 0.1 Mn 0.1 (NCM811), LiNi 0.85 Co 0.075 Mn 0.075 In one of them, the battery negative electrode material is one of graphite-based materials, silicon-based materials, tin-based materials or titanium-based materials.
16. The high-safety lithium-ion battery according to claim 15, characterized in that: The high thermal conductivity current collector and the metal tab on the battery are welded by brazing, including resistance welding, laser welding or electron beam welding, and the battery type is one of a button battery, a cylindrical battery, a square shell battery and a soft pack battery.
Citation Information
Patent Citations
Lithium ion battery current collector and lithium ion battery
CN104681820A
Preparation method of highly-graphited carbon nanotube ultrathin heat conduction and electric conduction film
CN106219519A
Lightweight high-conductivity flexible lithium battery current collector material, and preparation method and application thereof
CN111661838A